2004
DOI: 10.1103/physrevlett.92.045501
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Small Silicon Self-Interstitial Defects

Abstract: The combination of long-time, tight-binding molecular dynamics and real-time multiresolution analysis techniques reveals the complexity of small silicon interstitial defects. The stability of identified structures is confirmed by ab initio relaxations. The majority of structures were previously unknown, demonstrating the effectiveness of the approach. A new, spatially extended tri-interstitial ground state structure is identified as a probable nucleation site for larger extended defects and may be key for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 31 publications
7
71
0
Order By: Relevance
“…I 4 -A is the most stable configuration of tetra-interstitial clusters found in our simulations [33]. The most stable configuration found for the Si tri-interstitial cluster is not shown in figure 1 as its symmetry is not compatible with W or X PL centers, but it agrees with the most stable I 3 configuration found in previous studies [33,29]. The formation energies of I 3 defects shown in figure. 1 relative to the most stable configuration are 1.49 eV for the I 3 -I, 0.95 eV for the I 3 -X, 0.7 eV for the I 3 -V, and 0.34 eV for the I 3 -C. We have also found that the I 3 -I has higher formation energy than the I 3 -V [16], and in fact I 3 -I was not obtained from our CMD simulations.…”
Section: Defect Formation Energy and Donor Levelsupporting
confidence: 80%
See 1 more Smart Citation
“…I 4 -A is the most stable configuration of tetra-interstitial clusters found in our simulations [33]. The most stable configuration found for the Si tri-interstitial cluster is not shown in figure 1 as its symmetry is not compatible with W or X PL centers, but it agrees with the most stable I 3 configuration found in previous studies [33,29]. The formation energies of I 3 defects shown in figure. 1 relative to the most stable configuration are 1.49 eV for the I 3 -I, 0.95 eV for the I 3 -X, 0.7 eV for the I 3 -V, and 0.34 eV for the I 3 -C. We have also found that the I 3 -I has higher formation energy than the I 3 -V [16], and in fact I 3 -I was not obtained from our CMD simulations.…”
Section: Defect Formation Energy and Donor Levelsupporting
confidence: 80%
“…For the X center, all defect candidates have been obtained from the annealing simulations. We have found the so called "compact tri-interstitial" [14,29,30,31,16], I 3 -C in the following, with tetrahedral symmetry.…”
Section: Configuration Selection Based On Symmetrymentioning
confidence: 99%
“…All the other configurations have a much higher energy or correspond to the diinterstitial surrounded by another interstitial. The MEP for the diffusion of the tri-interstitial from its ground state 3V tetra to a neighbor 3V tetra needs the crossing of a 0.45 eV barrier coherent with previous work (0.49eV [22]) [21], whereas this barrier is 2.59 eV for the diffusion from a 3V block configuration to a 3V block configuration. For this reason, during annealing all the 3V tetra configurations diffuse, whereas the 3V block does not.…”
Section: The Tri-interstitial Defectsupporting
confidence: 67%
“…Problems within the range of semiquantitative understanding may include activation barriers of diffusion, interactions among point defects, and the properties of point defect clusters. 21 It also opens the possibility of studies of other systems where pure DFT methods have failed to reproduce the band structure, such as Ge and UO 2 , which the LDA and GGA predict to be metallic, but where the HSE functional accurately describes the gap. 22 Our results on defects are especially noteworthy as radiation damage and the resultant point defects play an important role in the properties of these technologically important materials.…”
mentioning
confidence: 99%